2020
DOI: 10.1007/s00382-020-05127-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the dynamics of the interannual variabilities of the wintertime East Asian Jet Core

Abstract: The East Asian jet has evident interannual variability in strength and position and has broad impacts on weather and climate in the Asian-Pacific-American region. In this study, we quantify the relative contributions of distinct dynamical processes responsible for the wintertime interannual variability of the East Asian jet core. The quantification is based on analyzing the zonal momentum budgets. Our budget analyses show distinct up-and downstream controls for the interannual intensification of the jet. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Change in atmospheric heat flux associated with seasonality of the two-circulation system is the primary cause of SST variations in this shallow area 28 . The extended winter regime with both dry and cold air and stronger wind speed accompanied by the southward shift of the WJ can maintain the vertical contrast between the local ocean and the atmosphere and cause excessive heat loss to the atmosphere, thereby decreased the SST 27 , 29 , 30 . In the meantime, the persisting summer regime associated with the northward migration of Westerly Jet would reduce the heat loss to the atmosphere, thereby increases the SST.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Change in atmospheric heat flux associated with seasonality of the two-circulation system is the primary cause of SST variations in this shallow area 28 . The extended winter regime with both dry and cold air and stronger wind speed accompanied by the southward shift of the WJ can maintain the vertical contrast between the local ocean and the atmosphere and cause excessive heat loss to the atmosphere, thereby decreased the SST 27 , 29 , 30 . In the meantime, the persisting summer regime associated with the northward migration of Westerly Jet would reduce the heat loss to the atmosphere, thereby increases the SST.…”
Section: Resultsmentioning
confidence: 99%
“…Even during the same season, the variations in SST in the study area may be related to the latitude where the WJ is placed. In previous studies, the 200 hPa wind vector corresponding to the WJ was reanalysed from the wind field data provided by NCEP and ERA-interim and compared with observed SST near the study area 30 , 40 . In a year when the WJ locates in relatively low latitudes from autumn to winter, the SSTs in the East Sea, Yellow Sea, and the East China Sea tend to decrease overall compared to other years.…”
Section: Discussionmentioning
confidence: 99%
“…Since the changes of background zonal wind can modulate the wave propagation and eddy generation which are important for the cut-off low amplification, we next explore the causes for the wind anomalies. Similar to the method in Chan et al (2020), we quantify the relative contributions of different dynamical processes (i.e., ageostrophic acceleration and zonal flow advection) by diagnosing the zonal momentum budget in Eq. ( 5).…”
Section: Possible Reason For Background Flow Changesmentioning
confidence: 99%
“…For example, using winter Monsoon Experiment (winter MONEX) twice-daily data, Chang and Lau [12] have shown that immediately after a cold surge (<1 day), the convection over the equatorial South China Sea intensifies, which causes a strengthening of the East Asian local Hadley circulation. In addition, Chan et al [43] reported that the local Hadley cell over East Asia plays a dominant role in the intensity variation of the East Asian jet stream. The enhanced East Asian local Hadley cell may potentially contribute to the strengthening of the East Asian jet stream during days 0-6 of the strong EAWM events (Figure 2d).…”
Section: Areamentioning
confidence: 99%